Revision of Fenestrobates (Acari, Oribatellidae) with description of F. marauni sp. nov., from South America, and new diagnosis for Oribatellidae - Ermilov, Sergey G.; Behan-Pelletier, Valerie M. (Zootaxa, 2014)
We propose a new species of the oribatid mite genus Fenestrobates (Oribatellidae), F. marauni sp. nov., based on adult specimens from Ecuador. The type species, F. capucinus Balogh and Mahunka, 1969 from Bolivia, is redescribed. We confirm the recombination of two species from the Russian Far East, F. rossicus Krivolutsky, 1974 from the Primorsky Region, and F. vicinus Ryabinin, 1975 from the Khabarovsk Region, as Oribatella rossicus (Krivolutsky) and O. vicinus (Ryabinin), and we give revised diagnoses for each. We present a new diagnosis for Fenestrobates and argue for its recognition as a genus distinct from Oribatella on the basis of the apomorphic development of a large, pouch-like depression positioned ventrally between pedotectum I and the lateral body wall, and absence of small ridges anteriorly on the notogaster. Based on these changes and new information, we give a revised diagnosis for Oribatellidae and provide a key to included genera.